Naturally Occurring Compounds Targeting Peroxisome Proliferator Receptors: Potential Molecular Mechanisms and Future Perspectives for Promoting Human Health - Maria Spanoudaki; Maria Chrysafi; Sousana K. Papadopoulou; Gerasimos Tsourouflis; Agathi Pritsa; Constantinos Giaginis (Applied Sciences)
Background: Peroxisome-proliferator-activated receptors (PPARs) constitute nuclear transcription factors controlling gene expression associated with cell growth and proliferation, diverse proteins, lipids, and glucose metabolism, being related to several other pathophysiological states such as metabolic disorders, atherogenesis, carcinogenesis, etc. The present survey aims to analyze the natural compounds that can act as agonists for the PPAR-α, PPAR-β/δ, and PPAR-γ system targeting, highlighting how the amazing biochemical diversity of natural compounds can yield new insights into this “hotspot” of the scientific field. Methods: A narrative review was performed by searching the recent international literature for the last two decades in the most authoritative scientific databases, like PubMed, Scopus, Web of Science, and Embase, using appropriate keywords. Results: Several natural compounds and/or their synthetic derivatives can act as ligands of PPARs, stimulating their transcriptional activity and enabling their use as preventive and/or therapeutic agents for several disease states, such as inflammation, oxidative stress, metabolic disturbances, atherogenesis, and carcinogenesis. Although synthetic compounds are increasingly used as drugs to manage health problems, serious side effects have been observed, while their natural analogues exhibit only few minor side effects. Conclusions: Further clinical studies on natural compounds such as ligands of PPARs and the evaluation of the related molecular mechanisms are needed to implement an effective strategy concerning the pharmaco-technology, food chemistry, and nutrition to introduce them as part of clinical and dietary practice.